Teknik Penerjemahan Google Translate dan Subtitle YouTube Indonesia Arab; Serial Nussa “Rarra Sakit” - Adelpina, Dea; Prissa, Salma Salsabila; Supriadi, Rinaldi (Study Program of Arabic Language Teaching, 2024)
This research analyzes translation techniques in the official YouTube subtitles for the